Transitions of motor neuron activities during Ciona development - Utsumi, Madoka K.; Oka, Kotaro; Hotta, Kohji (Frontiers in Cell and Developmental Biology, 2023)
Motor neurons (MNs) are one of the most important components of Central Pattern Generators (CPG) in vertebrates (Brown, Proceedings of The Royal Society B: Biological Sciences (The Royal Society), 1911, 84(572), 308–319). However, it is unclear how the neural activities of these components develop during their embryogenesis. Our previous study revealed that in Ciona robusta (Ciona intestinalis type A), a model organism with a simple neural circuit, a single pair of MNs (MN2L/MN2R) was determining the rhythm of its spontaneous early motor behavior (developmental stage St.22-24). MN2s are known to be one of the main components of Ciona CPG, though the neural activities of MN2s in the later larval period (St.25-) were not yet investigated. In this study, we investigated the neural activities of MN2s during their later stages and how they are related to Ciona’s swimming CPG. Long-term simultaneous Ca2+ imaging of both MN2s with GCaMP6s/f (St.22-34) revealed that MN2s continued to determine the rhythm of motor behavior even in their later larval stages. Their activities were classified into seven phases (I-VII) depending on the interval and the synchronicity of MN2L and MN2R Ca2+ transients. Initially, each MN2 oscillates sporadically (I). As they develop into swimming larvae, they gradually oscillate at a constant interval (II-III), then start to synchronize (IV) and fully synchronize (V). Intervals become longer (VI) and sporadic again during the tail aggression period (VII). Interestingly, 76% of the embryos started to oscillate from MN2R. In addition, independent photostimulations on left and right MN2s were conducted. This is the first report of the live imaging of neural activities in Ciona’s developing swimming CPG. These findings will help to understand the development of motor neuron circuits in chordate animals.